A novel octavalent combined Erysipelas, Parvo and Leptospira vaccine provides (cross) protection against infection following challenge of pigs with 9 different Leptospira interrogans serovars. Issue 1 (December 2015) - Jacobs, A.; Harks, F.; Hoeijmakers, M.; Segers, R.
Abstract Background In the present study the efficacy and cross protection of a novel ready-to-use combination vaccine, Porcilis® Ery + Parvo + Lepto, against swine leptospirosis, was investigated. The octavalent vaccine contains inactivated antigens ofErysipelothrix rhusiopathiae, Parvovirus and 6Leptospira interrogans sensu lato strains of serogroups Canicola, Icterohaemorrhagiae, Grippotyphosa, Australis (Bratislava), Pomona and Tarassovi. In this study ninety pigs were vaccinated twice with Porcilis® Ery + Parvo + Lepto at six and ten weeks of age and ninety age and source-matched animals served as unvaccinated control. Two weeks after booster vaccination, groups of vaccinated and control pigs (ten pigs per group) were challenged with fresh virulent cultures of either of the nine different challenge strains. Compared to the vaccine strains the challenge strains were heterologous strains of the same serovar or of a different serovar within the same serogroup. The challenge strains tested were of serovar Canicola, Icterohaemorrhagiae, Copenhageni (serogroup Icterohaemorrhagiae), Grippotyphosa, Bananal/Liangguan (serogroup Grippotyphosa), Pomona, Tarassovi and Vughia (serogroup Tarassovi). Results After the different challenges most control animals became leptospiraemic for 2–7 days. The vaccinated pigs remained blood culture negative except for two animals after serovar Icterohaemorrhagiae and two animals after serovar Tarassovi challenge which became leptospiraemic for only 1 day. The incidence of Leptospiraemia (as determined by blood culture) was significantly less in vaccinates compared to the controls after all challenges. The vaccine also prevented renal infection and urinary shedding after serovar Canicola challenge. The other serovars did not induce detectable renal infection or urinary shedding. Conclusion The present study demonstrates that the new combination vaccine Porcilis® Ery + Parvo + Lepto induces significant (cross) protection against nine different serovars within the serogroups Canicola, Icterohaemorrhagiae, Grippotyphosa, Australis (Bratislava), Pomona and Tarassovi.